Corporate environmental education as a contribution to strengthening business sustainability and raising employee awareness in the company (Revista Contexto & Educação, 2025)
This study aims to examine how organizations implement corporate environmental education, highlighting the practices and principles that contribute to organizational sustainability and employee awareness. To achieve these objectives, we employed a questionnaire using non-probability convenience sampling. Data was collected between October 3 and November 7, 2023, yielding 54 validated responses. The findings underscore the need for environmental education initiatives in corporate settings to be developed as continuous, interdisciplinary programs. Such initiatives should stimulate critical reflection among employees regarding business sustainability challenges while fostering an organizational culture of sustainability. This culture can facilitate dialogue, participation, and engagement among employees and stakeholders, ultimately advancing socio-environmental sustainability in the workplace.
Keywords: Corporate Environmental Education; Business Sustainability; Employee Awareness; Sustainable Practices